(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the results of early global stimulation in preterm children during home visits. Method: Qualitative research, action-research type, carried out during home visits and in partnership with the Family Health Strategy in a neighborhood on the outskirts of the city of Maceió, Alagoas. The evaluation and monitoring of two children linked to the ESF was carried out. Data were collected through semi-structured interviews and physical examination, using as a basis the charts and graphs provided by the Ministry of Health and in the light of Vigotski’s theoretical framework. Based on the findings, activities were planned and applied in partnership with the parents, over a period of four weeks, being carried out with the researcher once a week during this period, and with reassessment of the children in the last meeting. Results: It was evidenced that factors such as maternal age and income are factors that negatively influence child development. Likewise, the follow-up to the DC of premature infants in primary care does not occur satisfactorily, with consultations in the hospital environment being prioritized. Early global stimulation contributed positively to the children in the study, but when performed in the family’s daily life. Conclusion: The importance of a professional nurse is highlighted, not only in the surveillance of the DC, but also as an agent in carrying out early stimulation. As a limitation, the study brought a small number of children evaluated, and therefore, it is suggested to carry out research with an increased number for a more reliable evaluation.